Leveraging Emerging Technologies to Document Abuses and Amplify Marginalised Voices in Conflict Zones: Lessons from Afghanistan - Mohiqi, Murtaza (Serikat Pengajar Hak Asasi Manusia Indonesia, 2024)
This study critically examines the specific role of emerging technologies in safeguarding human rights amidst conflict, with a focus on Afghanistan as a compelling case study. Technology is explored not merely as a passive recorder but as an active agent of accountability, employing innovative applications like artificial intelligence and blockchain to ensure evidence integrity and strengthen legal recourse. Beyond traditional social media, the research highlights the transformative potential of technologies such as virtual reality and immersive storytelling in amplifying marginalised voices, providing these communities with platforms to share their experiences more effectively and engage global audiences. The study also investigates context-specific communication strategies, showcasing how secure channels, mesh networks, and satellite communication help overcome barriers in conflict zones and ensure resilient information flow and emergency response. By analysing the Afghanistan case study, the research offers a critical examination of the ethical challenges, operational barriers, and practical implications associated with deploying these technologies. This article contributes to the growing interdisciplinary literature at the intersection of technology, human rights, and conflict by offering one of the first comprehensive analyses of how diverse digital tools function not only as evidentiary instruments but as mechanisms of empowerment and protection in fragile settings. This analysis underscores the importance of a balanced and contextually nuanced approach, addressing not only the opportunities but also the limitations and risks—such as ethical concerns, sustainability, and accessibility—in leveraging technology for human rights protection. The findings offer actionable insights for policymakers, human rights practitioners, and technologists, providing a roadmap for strategically integrating technology into human rights efforts to create a more just and equitable response to conflict.